Unraveling Trichoderma species in attine ant environment: description of three new taxa - Vidaurre Montoya, Quimi [UNESP] (2015)
Fungus-growing attine ants forage diverse substrates to grow mutualistic fungi for food. In addition to the fungal partner, colonies of these insects harbor a rich microbiome composed of bacteria, filamentous fungi and yeasts. Previous studies investigated ecological aspects of filamentous fungi in gardens of leaf-cutter ants and reported some Trichoderma species; however, no studies systematically addressed the putative association of Trichoderma species with attine ants, especially in non-leafcutter ants. Here, a total of 68 strains of Trichoderma preserved in our collection were analyzed using three molecular markers (ITS, tef1 and rpb2). In addition, 30 out of 68 strains were also morphologically examined. The strains correspond to samples collected from leaf-cutter and non-leafcutter ants in 12 points from four states in Brazil and two points in Texas (USA), comprising the largest sampling carried out so far for Trichoderma in attine ant environment. Our results revealed the richness of Trichoderma in this environment, since we found 19 Trichoderma species, including three new species described in the present work (T. attinis, T. texana and T. longifialidicum). Moreover, we show that all 68 strains grouped within different clades across the Trichoderma phylogeny, which are identical or closely related to strains derived from several other environments, supporting for a transient nature of the genus Trichoderma in attine ant colonies. The discovery of three new species suggests that the dynamic foraging behavior of these insects might be responsible for accumulation of transient fungi into their colonies, which might hold several fungal taxa still unknown for science